2020
DOI: 10.1186/s12891-020-03510-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of negative-pressure wound therapy after total knee arthroplasty is effective for reducing complications and the need for reintervention

Abstract: Background: Wound healing complications are causal factors of prosthesis infection and poor postoperative evolution of patients after total knee arthroplasty (TKA). Negative-pressure wound therapy (NPWT) can be an option to minimize these complications. The aim of this study is to compare the complications of patients undergoing TKA who used a portable NPWT device in the immediate postoperative period with those of a control group. Methods: A total of 296 patients were evaluated. Patients were divided into two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
0
12
0
3
Order By: Relevance
“… 10 Among the comorbidities, it is worth noting that patients with diabetes mellitus had more complications in general, according to literature data, especially complications related to wound dehiscence and infections. 15 16 It was observed in the present study that patients with heart condition had a higher risk of developing arthrofibrosis, probably due to the difficulty in performing adequate rehabilitation, but further studies should be carried out to research this association. 3 13 No other comorbidity was able to independently change the overall risk of complications with statistical significance, probably due to the small sample size of the subgroups of those pathologies in the observed sample.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“… 10 Among the comorbidities, it is worth noting that patients with diabetes mellitus had more complications in general, according to literature data, especially complications related to wound dehiscence and infections. 15 16 It was observed in the present study that patients with heart condition had a higher risk of developing arthrofibrosis, probably due to the difficulty in performing adequate rehabilitation, but further studies should be carried out to research this association. 3 13 No other comorbidity was able to independently change the overall risk of complications with statistical significance, probably due to the small sample size of the subgroups of those pathologies in the observed sample.…”
Section: Discussionmentioning
confidence: 73%
“… 10 Dentre as comorbidades, vale notar que os pacientes portadores de diabetes mellitus apresentaram mais complicações em geral segundo dados da literatura, especialmente as complicações relacionadas com deiscência de feridas e infecções. 15 16 Observou-se no presente estudo que pacientes cardiopatas apresentaram maior risco de desenvolver artrofibrose, provavelmente por dificuldade de realizar uma reabilitação adequada, mas novos estudos devem ser realizados para investigas tal associação. 3 13 Nenhuma outra comorbidade foi capaz de alterar o risco de complicações em geral com significância estatística independentemente, provavelmente devido ao pequeno tamanho amostral dos subgrupos destas patologias na amostra observada.…”
Section: Discussionunclassified
“…[131][132][133] In contrast, both randomized controlled trials that made this comparison reported decreased SSI rates in patients who received NPWT compared with standard occlusive dressings. 46,134 Among the four studies that evaluated the PICO system, [135][136][137][138] three reported decreased SSI rates and one found similar rates between groups (see ►Table 5).…”
Section: Surgical Incise Drapingmentioning
confidence: 99%
“…Major complications, such as deep infection, loosening, and instability, often require revision surgery, whereas minor complications, such as discomfort around the scar [ 10 ] and noise from the knee [ 11 ], seldom require revision. In addition, minor complications related to wounds are relatively common [ 12 ], and wound-related complications have potential risks of developing into major complications that require further surgery. Other researchers have reported that 46–98% of patients who underwent knee replacement complained of numbness around the knee postoperatively [ 10 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%